The Mesozoic flora of Graham Land - Halle, Thore Gustaf, b. 1884; Svenska sydpolar-expeditionen (1901-1903) (Stockholm : Lithographisches Institut des Generalstabs; [etc., etc.], 1913)
Mode of access: Internet.